Compressive Fracture Resistance of Porcelain Laminates Bonded to Enamel or Dentin with Four Adhesive Systems - Morakot Piemjai, DDS, MDSc, PhD; (Journal of Prosthodontics, 2007)
The addition of anionic charge on denture base resins has been shown to inhibit Candida albicans adhesion and to facilitate adsorption of salivary defense molecules.